2020
DOI: 10.1111/jasp.12710
|View full text |Cite
|
Sign up to set email alerts
|

Rational and moral motives to reduce red and processed meat consumption

Abstract: Western diets are characterized by excessive red and processed meat consumption (RPMC), which has several environmental negative consequences, such as risky pollution, depletion, and the disruption of water and land resources (e.g., Gardner, Hartle, Garrett, Offringa, & Wasserman, 2019). To reduce these effects, public policies should effectively communicate the urgency of a shift to a less animal-based diet. However, there is little agreement over the degree to which public policies should leverage either rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 66 publications
2
36
0
1
Order By: Relevance
“…The theoretical starting point of our study was the integration of psychosocial models aimed at explaining behavior planning, its change through persuasive communication, and the matching effect between persuasive messages and recipients' characteristics (see also Di Massimo et al, 2019 ; Carfora et al, 2020a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical starting point of our study was the integration of psychosocial models aimed at explaining behavior planning, its change through persuasive communication, and the matching effect between persuasive messages and recipients' characteristics (see also Di Massimo et al, 2019 ; Carfora et al, 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…Subjective norm was assessed with three items using a Likert scale [e.g., “Most of the people important to me (partners, family, friends) think I should do physical exercises at home regularly… Strongly disagree (1)—Strongly agree (7)”; adapted from Carfora et al, 2020a , b ]. The three items were used to compute a single subjective norm index, with higher scores indicating a higher level of it.…”
Section: Methodsmentioning
confidence: 99%
“…In the domain of communication research, many scholars have investigated how to overcome the aforementioned psychological barriers, with message interventions focused on health, environmental, and ethical issues connected to high red/processed meat consumption (from now on RPMC) (e.g., Bertolotti et al, 2016 ; Carfora et al, 2019a , b ; Stea and Pickering, 2019 ; Harguess et al, 2020 ). Only limited research has been devoted to the effects on attitude and intentions of messages framed in terms of the valence of the expected outcomes (i.e., in terms of gain, non-loss, non-gain, or loss; Di Massimo et al, 2019 ; Carfora et al, 2020a ). In addition, so far, no scholars have considered the cognitive and emotional processing underlying the effects of such message framing (Rothman and Baldwin, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of consequences is considered as a cognitive precondition to moral norm activation, which is the feeling of being responsible for the negative impact of the nonimplementation of pro-environmental behaviors. Accordingly, many scholars have confirmed that people's awareness of consequences influences the ascription of responsibility in several pro-environmental domains [6,8,78]. In the case of sustainable clothing, different scholars focused on the relationship between awareness of consequences and purchasing intention, showing that peoples' environmental awareness has a strong positive influence on purchase intention related to sustainable fashion [53,59,74].…”
Section: Hypothesis 8 (H8) General Pro-environmental Beliefs Influence Awareness Of Consequencesmentioning
confidence: 99%
“…Specifically, through reduced consumption and a switch to goods with less carbon emission during production and use, the European Union could reduce its carbon footprint by about 25% [3]. To reach this goal, most of the social science literature has focused on sustainable behaviors related to transport, building, and food [4], such as reduced energy consumption and sustainable food choices [5][6][7][8]. In this field of study, sustainable clothing purchase has been less investigated [9], even if fashion supply chains are similarly responsible for a negative environmental impact-due to significant carbon footprints through toxic dyes, excessive waste, chemical usage, and water contamination [9,10].…”
Section: Introductionmentioning
confidence: 99%